Effect of Gestational Homocystein on Fetal Growth in Bangladeshi Women (Ibrahim Medical College Journal, 2009)
Hyperhomocysteinemia has been reported among the women of south Asian countries including Bangladesh. It affects fetal development through intrauterine growth retardation (IUGR) and is one of the important issues associated with low birth weight (LBW) of newborns. If its association with IUGR can be established, then maternal serum Hcy could help diagnose IUGR cases and ultimately provide scope for prevention and treatment of the cases by supplementation of B-vitamins and folic acid. In this case control study, 80 pregnant women were enrolled, of which 30 were IUGR cases while 50 appropriate for gestational age (AGA) pregnancies worked as control. Maternal Hcy at 3rd trimester of all the subjects were measured and its effects on neonatal size were analyzed. The maternal Hcy of the IUGR cases was significantly higher than the control. The babies born to IUGR cases had a significantly lower birth weight, lower height and lower OFC compared to the babies born to control mothers. Weight, length and OFC of the newborns showed significant inverse correlation with maternal Hcy. Hyperhomocysteinemia was found to be a significant risk factor for LBW (OR 5.23, 95% CI 1.92-14.23), short stature (OR 2.19, CI 0.792-6.06 ) and low OFC (OR 3.04, CI 1.15-8.04) of the newborns. Ibrahim Med. Coll. J. 2009; 3(1): 13-16 Keywords: Homocysteine, intrauterine growth restriction, low birth weight, pregnancy.   doi: 10.3329/imcj.v3i1.2912